2012
DOI: 10.1038/nature11114
|View full text |Cite|
|
Sign up to set email alerts
|

The deubiquitinase USP9X suppresses pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDA) remains a lethal malignancy despite tremendous progress in its molecular characterization. Indeed, PDA tumors harbor four signature somatic mutations1–4, and a plethora of lower frequency genetic events of uncertain significance5. Here, we used Sleeping Beauty (SB) transposon-mediated insertional mutagenesis6,7 in a mouse model of pancreatic ductal preneoplasia8 to identify genes that cooperate with oncogenic KrasG12D to accelerate tumorigenesis and promote progression. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
317
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 293 publications
(333 citation statements)
references
References 36 publications
13
317
3
Order By: Relevance
“…Previous studies have demonstrated that USP9X has different target substrates in different cell types. One study showed that USP9X promotes cell survival by stabilizing Mcl1 in a deubiquitination-dependent manner in human lymphoma (20), whereas a more recent report showed that USP9X expression is inversely linked with pancreatic cancer by acting as a tumor suppressor (21). It seems that USP9X does not play a role in T-cell survival, as revealed in the present study.…”
Section: Discussionsupporting
confidence: 32%
See 1 more Smart Citation
“…Previous studies have demonstrated that USP9X has different target substrates in different cell types. One study showed that USP9X promotes cell survival by stabilizing Mcl1 in a deubiquitination-dependent manner in human lymphoma (20), whereas a more recent report showed that USP9X expression is inversely linked with pancreatic cancer by acting as a tumor suppressor (21). It seems that USP9X does not play a role in T-cell survival, as revealed in the present study.…”
Section: Discussionsupporting
confidence: 32%
“…Recent studies have reported that USP9X plays important role in the regulation of cell survival and TGF-β signaling by deubiquitinating myeloid leukemia cell differentiation protein 1 (Mcl1), Itch, and Smad4 (20)(21)(22); however, the function of USP9X in the immune system, particularly in T-cell regulation, remains unknown. In this study, we identified USP9X as a critical positive regulator of TCR signaling pathway and characterized the function of USP9X by genetic, molecular, and immunologic studies.…”
mentioning
confidence: 99%
“…Indeed, recent reports suggest both tumour promoting as well as tumour suppressive functions for USP9X in different contexts 7,37 . It will be relevant in the future to identify the factors that dictate the positive or negative contribution of USP9X to tumorigenesis, and govern its substrate specificity and recruitment, and to study how its cellular distribution may regulate its availability for interacting proteins.…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong overlap between the orthologues of genes identified in mouse insertional mutagenesis screens and human oncogenes and tumour suppressor genes, validating the use of these screening strategies [41,47,49,51]. Furthermore, insertional mutagenesis has facilitated the identification of novel cancer genes, such as the oncogene Pim1 [52] and the pancreatic tumour suppressor gene Usp9x [53] -cancer genes identified in the mouse before being found to be relevant for human tumourigenesis. By performing these screens on a cancer pre-disposed background, insertional mutagenesis screens may reveal information about the underlying mechanisms of synergy between oncogenic and tumour suppressor pathways.…”
Section: Van Der Weyden and Dj Adamsmentioning
confidence: 97%